2012
DOI: 10.1021/jp210227s
|View full text |Cite
|
Sign up to set email alerts
|

For the Sequence YKGQ, the Turn and Extended Conformational Forms Are Separated by Small Barriers and the Turn Propensity Persists Even at High Temperatures: Implications for Protein Folding

Abstract: The folding of the sequence (21)DTVKLMYKGQPMTFR(35) from staphylococcal nuclease into a β-hairpin, nucleated by the turn region YKGQP, is known to be an early folding event. With YKGQ being the shortest sequence for a β-turn model and in view of its importance to the folding of staphylococcal nuclease, we investigated the thermodynamics of turn formation at a range of temperatures from 280 to 380 K, with a regular interval of 10 K. Eleven independent molecular dynamics simulations (under NPT conditions) were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…This observation indicates that the population of turn conformations might not be very temperature dependent, in agreement with recent theoretical predictions and experimental results. 83, 91 For the C-terminal residue, we obtained pPII fractions of 0.67, 0.60, for cationic and zwitterionic AAA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicates that the population of turn conformations might not be very temperature dependent, in agreement with recent theoretical predictions and experimental results. 83, 91 For the C-terminal residue, we obtained pPII fractions of 0.67, 0.60, for cationic and zwitterionic AAA, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is a very surprising result since one would naively expect that turn‐like structures are entropically disfavored and therefore less likely to be populated at higher temperatures. However, a recent computational study aimed at exploring the behavior of the YKGQ sequence in a hairpin‐forming peptide found that it can form turns at low (room) as well as at high temperature because enthalpy and entropy are both stabilizing 66…”
Section: Resultsmentioning
confidence: 99%
“…The values for Δ G ( T R ) were calculated from the pPII/β mole fraction ratio obtained from the conformational analysis . Eqn is based on the experimentally backed assumption that even in the presence of multiple conformers, the temperature dependence of the Gibbs energy landscape can practically be accounted for by a two‐state model, which assumes that the population of minor turn fractions does not change with temperature …”
Section: Methodsmentioning
confidence: 99%